Cu2-xSe-Pt nano material, microneedle patch, preparation method and application

Through in situ modification of Cu2-xSe@Pt nanomaterials, combined with photothermal conversion and Fenton catalysis, the problem of killing multidrug-resistant bacteria by existing antibacterial strategies was solved, efficient antibacterial treatment and deep drug delivery were achieved, and cytotoxicity was reduced.

CN120617510APending Publication Date: 2025-09-12THE FIRST AFFILIATED HOSPITAL OF ARMY MEDICAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510848168.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing single-mode antibacterial strategies cannot effectively kill multidrug-resistant bacteria, and nanozymes have cytotoxicity problems, making it difficult to achieve deep drug delivery.

Method used

Using Cu2-xSe@Pt nanomaterials, by in situ modification of Pt single atoms, combined with photothermal conversion and Fenton catalysis, synergistic antibacterial treatment of PTT and CDT is achieved, reducing cytotoxicity and improving drug delivery efficiency.

Benefits of technology

Under the synergistic effect of PTT and CDT, Cu2-xSe@Pt nanomaterials significantly improved the antibacterial effect, reduced cytotoxicity, and achieved efficient deep drug delivery and rapid sterilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120617510A_ABST
    Figure CN120617510A_ABST
Patent Text Reader

Abstract

The invention relates to a Cu2-xSe-Pt nano material, a microneedle patch, a preparation method and application. The Cu < 2-x > Se (at) Pt nano material is composed of a Cu < 2-x > Se nanosphere and platinum modified on the surface of the Cu < 2-x > Se nanosphere in situ. The invention provides a preparation method of a Cu2-xSe-Pt nano-material, which comprises the following steps: adding PSS, SeO2 and AA into water, heating and stirring, adding copper salt and AA, reacting, and adding water and a hexachloroplatinic acid solution to obtain the Cu2-xSe-Pt nano-material. The invention provides an application of a Cu < 2-x > Se (at) Pt nano material. The invention also provides a microneedle patch as well as a preparation method and application thereof. The invention provides a novel material for resisting multi-drug-resistant bacteria, which solves the problems that the existing single antibacterial strategy is limited and the expected curative effect cannot be achieved, also solves the problem of cytotoxicity of the existing nano enzyme, realizes deep drug delivery, ensures efficient local drug release and avoids systemic toxicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a Cu 2-x Se@Pt nanomaterials, microneedle patches, preparation methods and applications. Background Art

[0002] Pathogenic microbial infections, especially those caused by bacteria, have become a major challenge to global public health, posing a serious threat to human health and life. It is estimated that hundreds of millions of people worldwide are affected by bacterial infections each year. According to the World Health Organization, a few common bacterial infections, such as pneumonia, urinary tract infections, and sepsis, alone result in millions of hospitalizations and hundreds of thousands of deaths each year. Currently, clinical treatment relies primarily on antibiotics for bactericidal treatment. However, the long-term, high-dose use of antibiotics can lead to excessive stimulation and accelerate the evolution of drug-resistant bacteria, resulting in bacterial resistance to multiple antibiotics and making some diseases difficult to cure. Therefore, developing new and effective treatment strategies for multidrug-resistant (MDR) bacteria has become a key task for researchers worldwide to combat drug-resistant bacterial infections and curb their spread.

[0003] With the rapid development of nanotechnology, a variety of emerging strategies based on multifunctional nanomaterials have been widely applied to treat multidrug-resistant (MDR) bacterial infections. Nanomaterials have emerged as a novel class of antimicrobial agents due to their high surface area, broad-spectrum antimicrobial activity, resistance to drug resistance, and low biotoxicity. Their mechanism of action primarily involves direct interaction with the bacterial cell wall, disrupting the cell membrane structure and ultimately inducing rapid bacterial death. In recent years, photothermal therapy (PTT) and chemodynamic therapy (CDT) using antimicrobial nanomaterials have garnered widespread attention due to their unique advantages and have emerged as promising therapeutic strategies for treating MDR bacterial infections. CDT achieves its bactericidal effect by catalyzing the conversion of H₂O₂ into highly cytotoxic reactive oxygen species (ROS), such as •OH, through Fenton / Fenton-like reactions. Nanozymes based on transition metals such as copper (Cu), manganese (Mn), and zinc (Zn) can induce membrane lipid damage at the site of bacterial infection, ultimately killing multidrug-resistant bacteria by inducing DNA fragmentation, protein denaturation, and irreversible oxidative damage to other cellular components. During PTT, laser irradiation of a photothermal agent converts the laser light into a large amount of heat, generating localized hyperthermia to eliminate bacteria and promote wound healing. PTT can non-invasively generate high temperatures within the bacteria's bioactive substrates (such as proteins and nucleic acids), disrupting the bacteria's intact structure, making it easier for antimicrobial agents to penetrate and kill protected bacteria.

[0004] However, single-modality antimicrobial strategies have limitations and often fail to achieve the desired therapeutic effect. When used alone, PTT can easily trigger an abnormal inflammatory response due to the prolonged, high-power exposure of near-infrared lasers. Similarly, CDT is often limited by microenvironmental factors such as pH and H2O2 concentration, which can easily lead to insufficient production of reactive oxygen species (ROS), preventing the bactericidal process. Therefore, combining PTT with CDT is becoming an effective and feasible approach to enhance antimicrobial efficacy. Summary of the Invention

[0005] In view of this, the object of the present invention is to provide a Cu 2-x Se@Pt nanomaterials, microneedle patches, preparation methods and applications provide a new type of nanomaterial that can resist multidrug-resistant bacteria, solving the problem that the existing single-mode antibacterial strategy is limited and cannot achieve the expected therapeutic effect. It can also solve the cytotoxicity problem of existing nanozymes and achieve deep drug delivery, ensuring efficient local drug release and avoiding systemic toxicity.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A Cu 2-x Se@Pt nanomaterials, composed of Cu 2-x Se nanospheres and in situ modification of the Cu 2-x Pt composition on the surface of Se nanospheres; Among them, the value of x is: 0 <x<2。

[0007] According to the above technical means, the Cu 2-x Se@Pt nanomaterials, composed of Cu 2-x Se nanospheres and in situ modification on Cu 2-x The Pt composition on the surface of Se nanospheres was determined by experiments. 2-x Se has excellent photothermal conversion performance and can be used as a p-type semiconductor nanocrystal. The cation holes induced by copper defects can interact with the electromagnetic field of light through localized surface plasmon resonance (LSPR) to convert light energy into heat energy. In addition, due to the coexistence of Cu (II) and Cu (I), Cu 2-x Se has a peroxidase-like efficient Fenton catalytic activity and can be used as a Fenton-like reagent for CDT. 2-xWhile improving the photothermal performance of Se, the catalytic performance is effectively improved by in-situ modification of Pt, which can effectively be applied to the synergistic antibacterial treatment of CDT and PTT. The combined effect of PTT (local high temperature destroys bacterial structure) and CDT (catalyzes H2O2 to generate ROS) overcomes the defects of single therapy and solves the problem that the existing single-mode antibacterial strategy is limited and cannot achieve the expected therapeutic effect. The introduction of single-atom Pt also reduces the reaction energy barrier of the catalytic reaction and effectively improves the reaction rate. At the same time, Cu 2-x Although Se has antibacterial activity, it also has high physiological toxicity, which limits its clinical application. In this application, the Pt single atom modification was used to optimize the Cu 2-x The surface properties of Se significantly reduce its cytotoxicity (100 μg / mL has been proven to be non-toxic by experiments), solving the cytotoxicity problem of existing nanozymes.

[0008] Cu 2-x In Se@Pt nanomaterials, Cu represents copper, Se represents selenium, and Pt represents platinum.

[0009] Preferably, the Pt is loaded in the form of atoms on the Cu 2-x Surface of Se nanospheres.

[0010] Preferably, the value of x is 0 or 1.

[0011] The present invention also provides a Cu 2-x The preparation method of Se@Pt nanomaterials comprises the following steps: S1. Add sodium polystyrene sulfonate (PSS), selenium dioxide (SeO2) and ascorbic acid (AA) to water, then stir under the first temperature, raise the temperature to the second temperature, add a mixed solution of copper salt and ascorbic acid (AA) under stirring, vigorously stir the reaction to obtain a green solution, centrifuge, wash, purify, and obtain Cu 2-x Se; S2, to Cu 2-x Add water and hexachloroplatinic acid (H2PtCl6) solution to Se, stir the reaction, centrifuge, wash, and purify to obtain Cu 2-x Se@Pt nanomaterials.

[0012] By in situ reduction method, Pt single atoms were integrated into Cu 2-x Se surface, thereby forming Cu 2-x Se@Pt nanoparticles improve their catalytic performance and photothermal conversion ability. And the experimental verification shows that when Cu is exposed to near-infrared irradiation in the presence of H2O2, 2-x Se@Pt shows a significant photothermal effect, which leads to a significant increase in temperature. 2-xSe@Pt catalyzes the conversion of H2O2 into a large amount of ROS, further enhancing the activity of CDT through a Fenton-like reaction. In addition, the catalytic reaction mediated by nanozymes is susceptible to temperature, and high temperature can promote the generation of ROS during the catalytic process. Sufficient heat from PTT and ROS generated by CDT can cause bacterial death. Ultimately, Cu 2-x Se@Pt exhibited a strong antibacterial effect against MDR bacteria, fully demonstrating its great potential as a PTT-CDT synergistic and highly effective antibacterial agent.

[0013] Preferably, the first temperature is 25-35° C., and the stirring time under the first temperature condition is 8-12 min.

[0014] Preferably, the first temperature is 30° C., and the stirring time under the first temperature condition is 10 min.

[0015] Preferably, the second temperature is 40-50°C.

[0016] Preferably, the second temperature is 45°C.

[0017] Preferably, in S1, the temperature of the vigorous stirring reaction is 40-50° C. and the time is 7-9 h.

[0018] Preferably, in S1, the temperature of the vigorous stirring reaction is 45° C. and the time is 8 h.

[0019] Preferably, in S2, the stirring reaction is carried out at room temperature for 0.8 to 1.2 hours.

[0020] Preferably, in S2, the stirring reaction time is 1 h.

[0021] Preferably, the copper salt is selected from copper sulfate and / or copper sulfate pentahydrate (CuSO4•5H2O).

[0022] Preferably, the molar ratio of copper salt to ascorbic acid (AA) in the mixed solution of copper salt and ascorbic acid (AA) is 1:4.

[0023] The present invention also provides a Cu prepared by the preparation method of the present invention. 2-x Application of Se@Pt nanomaterials, the Cu 2-x Se@Pt nanomaterials are used to prepare drugs against drug-resistant bacteria.

[0024] Preferably, the Cu 2-x Se@Pt nanomaterials as photothermal conversion materials.

[0025] Preferably, the Cu 2-x Se@Pt nanomaterials are used as p-type semiconductor nanocrystal materials.

[0026] Preferably, the Cu 2-x Se@Pt nanomaterials as Fenton-like reagents.

[0027] Preferably, the Cu 2-x Se@Pt nanomaterials as nanozymes.

[0028] Preferably, the drug-resistant bacteria include carbapenem-resistant bacteria and methicillin-resistant bacteria.

[0029] Carbapenem-resistant bacteria include Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli, while methicillin-resistant bacteria include Staphylococcus aureus.

[0030] The present invention also provides a microneedle patch, comprising hyaluronic acid and Cu prepared by the preparation method of the present invention. 2- x Se@Pt nanomaterials.

[0031] The present invention also provides a method for preparing a microneedle patch, comprising the following steps: 1) Cu 2-x Se@Pt nanomaterials were dissolved in a photoinitiator, and hyaluronic acid was added to obtain a mixed solution; 2) The mixed solution is loaded into a mold, defoamed, vacuum-filled, dried, irradiated with ultraviolet light, and demolded to obtain a hydrogel microneedle patch.

[0032] Experiments have demonstrated that the hydrogel microneedle patch produced by the present method can efficiently generate reactive oxygen species, achieving rapid and efficient sterilization. It can also penetrate biomembranes and achieve deep drug delivery, ensuring efficient local release while avoiding systemic toxicity. This effectively addresses the difficulty of traditional biomaterials in penetrating biomembranes and achieving deep tissue treatment, improving treatment precision and providing a new option for rapid wound treatment.

[0033] Preferably, the photoinitiator is selected from lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).

[0034] Preferably, the hyaluronic acid is selected from methacryloyl hyaluronic acid (HAMA).

[0035] Preferably, the drying temperature is 30-40° C., and the drying time is 1.5-4.5 h.

[0036] Preferably, the wavelength of the ultraviolet lamp is 365 nm, and the irradiation time is 8 to 12 minutes.

[0037] Preferably, the method for preparing the microneedle patch comprises the following steps: 1) Cu 2-xSe@Pt powder was dissolved in a 0.25 wt% photoinitiator lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) solution to a final concentration of 40 μg / ml, and then methacryloylated hyaluronic acid (HAMA) powder was added to a final concentration of 25 mg / ml. The solution was dissolved and defoamed overnight to obtain Cu 2-x Se@Pt-HAMA mixed solution; 2) Add the Cu synthesized in step 1) to the cleaned PDMS template 2-x 400 μl of Se@Pt-HAMA mixed solution was repeatedly defoamed and vacuum filled (2-3 times), then dried at 35 °C for 2 h, and then 200 μl of Cu was added. 2-x The Se@Pt-HAMA mixed solution was defoamed and dried for 2 h. The drying and concentration process was repeated 2-3 times. Then, it was irradiated with a UV lamp at a wavelength of 365 nm for 10 min and finally demolded to obtain Cu 2-x Se@Pt / MN hydrogel microneedle patch, stored dry.

[0038] The present invention also provides a use of the microneedle patch prepared by the preparation method of the present invention in preparing drugs for resisting drug-resistant bacteria.

[0039] Beneficial effects of the present invention: Cu of the present invention 2-x Se@Pt nanomaterials not only have Cu 2-x Se has excellent photothermal conversion performance and can also be modified with Pt in situ, thus having a peroxidase-like efficient Fenton catalytic activity. Therefore, it is effectively applied in CDT and PTT synergistic antibacterial treatment, using the combined effect of PTT (local high temperature to destroy bacterial structure) and CDT (catalyzing H2O2 to generate ROS) to overcome the defects of single therapy. The introduction of single-atom Pt also reduces the reaction energy barrier of the catalytic reaction, effectively improving the reaction rate. At the same time, the Cu 2-x The surface properties of Se significantly reduced its cytotoxicity.

[0040] Cu of the present invention 2-x Preparation method of Se@Pt nanomaterials, integrating Pt single atoms into Cu by in situ reduction method 2-x Se surface, thereby forming Cu 2-x Se@Pt nanoparticles improve their catalytic performance and photothermal conversion ability. And the experimental verification shows that when Cu is exposed to near-infrared irradiation in the presence of H2O2, 2-x Se@Pt shows a significant photothermal effect, which leads to a significant increase in temperature. 2-xSe@Pt catalyzes the conversion of H2O2 into a large amount of ROS, further enhancing the CDT activity through a Fenton-like reaction. In addition, the catalytic reaction mediated by nanozymes is susceptible to temperature, and high temperature can promote the generation of ROS during the catalytic process. Sufficient heat from PTT and ROS generated by CDT can cause bacterial death. 2-x Se@Pt exhibited a strong antibacterial effect against MDR bacteria, fully demonstrating its great potential as a PTT-CDT synergistic and highly effective antibacterial agent.

[0041] The hydrogel microneedle patch produced by the method of the present invention can achieve efficient generation of reactive oxygen species, achieving rapid and efficient sterilization. It can also penetrate biomembranes and achieve deep drug delivery, ensuring efficient local drug release, avoiding systemic toxicity, and improving treatment accuracy. This provides a new option for rapid wound treatment. Furthermore, the preparation method of this hydrogel microneedle patch is simple, the raw materials are readily available, the cost is low, and it is easy to mass-produce and apply. It has great application value in the field of biomedical materials technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The Cu prepared in Example 1 2-x Se and Cu 2-x TEM images of Se@Pt NPs; Figure 2 The Cu prepared in Example 1 2-x Se and Cu 2-x XRD patterns of Se@Pt NPs; Figure 3 The Cu prepared in Example 1 2-x High-resolution XPS spectrum of Cu 2p orbitals of Se; Figure 4 The Cu prepared in Example 1 2-x High-resolution XPS spectrum of Cu 2p orbitals of Se@Pt NPs; Figure 5 The Cu prepared in Example 1 2-x High-resolution XPS spectrum of Pt 4f orbitals of Se@Pt NPs; Figure 6 The Cu prepared in Example 1 2-x Catalytic kinetic results of Se@Pt NPs; Figure 7 Pt and Cu prepared in Example 1 2-x Se and Cu 2-x Gibbs free energy change diagram of Se@Pt NPs catalyzed H2O2 reaction; Figure 8 The Cu prepared in Example 1 was captured by DMPO. 2-xElectron paramagnetic resonance (EPR) spectra of •OH (hydroxyl radical) in Se@Pt NPs and H2O2 solution; Figure 9 The Cu prepared in Example 1 was captured by TEMP. 2-x Electron paramagnetic resonance (EPR) spectra of ¹O2 (singlet oxygen) in Se@Pt NPs and H2O2 solution; Figure 10 To detect the Cu prepared in Example 1 using TMB probe 2-x Catalase-like performance results of Se@Pt NPs in the presence of different concentrations of H2O2; Figure 11 The Cu prepared in Example 1 under 808 nm laser irradiation 2-x Temperature rise curves of Se@Pt NPs (100 μg / ml) at different laser intensities; Figure 12 808 nm laser (1 W / cm 2 ) irradiated with different concentrations of Cu prepared in Example 1 2-x Temperature rising curve of Se@Pt NPs; Figure 13 808 nm laser (1 W / cm 2 ) irradiated, H2O, Cu prepared in Example 1 2-x Se (100 μg / ml) and Cu 2-x Thermal imaging of Se@Pt NPs (100 μg / ml); Figure 14 The Cu prepared in Example 4 2-x Optical image and SEM image of Se@Pt / MN; Figure 15 The Cu prepared in Example 4 2-x Thermal imaging of Se@Pt / MN (808 nm, 1W / cm 2 ); Figure 16 The Cu prepared in Example 4 2-x Temperature variation curve of Se@Pt / MN (808 nm, 1W / cm 2 )picture; Figure 17 The Cu prepared in Example 4 2-x Mechanical strength curve of Se@Pt / MN; Figure 18 The Cu prepared in Example 4 2-x Se@Pt / MN as nanozyme release efficiency results; Figure 19The Cu prepared in Example 1 2-x Se and Cu 2-x Figure 3. In vitro antibacterial results of Se@Pt NPs. Figure 20 The Cu prepared in Example 1 2-x Se and Cu 2-x Antibacterial mechanism of Se@Pt NPs: Live-dead staining results; Figure 21 Schematic diagram of the treatment process for MRSA-infected wounds; Figure 22 This is the result of the MRSA infection wound healing experiment. DETAILED DESCRIPTION

[0043] The following will describe the embodiments of the present invention with reference to preferred embodiments. Those skilled in the art will readily appreciate the other advantages and benefits of the present invention from the disclosure herein. The present invention may also be implemented or applied through various other specific embodiments, and the details in this specification may be modified or altered based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are intended only to illustrate the present invention and are not intended to limit the scope of protection of the present invention.

[0044] Example 1 A Cu 2-x The preparation method of Se@Pt nanomaterials comprises the following steps: S1. Take 5.5 mL of H2O and add it to a round-bottom flask. Then, add 1.6 mL of 10 mg / mL PSS (sodium polystyrene sulfonate), 0.1 mL of 0.2 mol / L SeO2 and 0.3 mL of 0.4 mol / L AA (ascorbic acid) in sequence, and stir at 30°C for 10 minutes. Then, heat the mixture to 45°C and add 0.1 mL of 0.4 mol / L CuSO4•5H2O and 0.4 mL of 0.4 mol / L AA mixed solution under vigorous stirring to obtain a mixture. The obtained mixture is vigorously stirred at 45°C for 8 hours until a green solution is obtained. The obtained green solution is centrifuged at 10,000 rpm for 10 minutes. The precipitate obtained by centrifugation is washed twice with ultrapure water and then purified by 10 kDa dialysis membrane for 24 hours. The purified product Cu 2-x Se was freeze-dried; S2, the Cu obtained in S1 2-x Se was dissolved in water to prepare a concentration of 1 mg / mL Cu 2-xSe solution, dissolve hexahydrate chloroplatinic acid (H2PtCl6·6H2O) in water to prepare a H2PtCl6 solution with a mass percentage of 0.015 wt%; Add 1 mL of 1 mg / mL Cu 2-x Se solution, then add 8 mL of ultrapure water, add 0.8 mL of 0.015 wt% H2PtCl6 solution under stirring at 450 rpm, stir at room temperature for 1 hour, centrifuge the resulting solution at 12000 rpm for 10 minutes, wash the precipitate obtained by centrifugation twice with ultrapure water to obtain purified Cu 2-x Se@Pt nanomaterials, namely Cu 2-x Se@Pt NPs; purified Cu 2-x Se@PtNPs were freeze-dried in a vacuum environment and redispersed in ultrapure water to prepare a Cu solution with a concentration of 1 mg / mL. 2-x Se@Pt NPs solution for subsequent use.

[0045] Example 2 A Cu 2-x The preparation method of Se@Pt nanomaterials comprises the following steps: S1. Take 5.5 mL of H2O and add it to a round-bottom flask. Then, add 1.6 mL of 10 mg / mL PSS (sodium polystyrene sulfonate), 0.1 mL of 0.2 mol / L SeO2 and 0.3 mL of 0.4 mol / L AA (ascorbic acid) in sequence, and stir at 30°C for 10 minutes. Then, heat the mixture to 45°C and add 0.1 mL of 0.4 mol / L CuSO4•5H2O and 0.4 mL of 0.4 mol / L AA mixed solution under vigorous stirring to obtain a mixture. The obtained mixture is vigorously stirred at 45°C for 8 hours until a green solution is obtained. The obtained green solution is centrifuged at 10,000 rpm for 10 minutes. The precipitate obtained by centrifugation is washed twice with ultrapure water and then purified by 10 kDa dialysis membrane for 24 hours. The purified product Cu 2-x Se was freeze-dried; S2, the Cu obtained in S1 2-x Se was dissolved in water to prepare a concentration of 1 mg / mL Cu 2-x Se solution, dissolve hexahydrate chloroplatinic acid (H2PtCl6·6H2O) in water to prepare a H2PtCl6 solution with a mass percentage of 0.15 wt%; Add 1 mL of 1 mg / mL Cu 2-xSe solution, then add 8 mL of ultrapure water, add 0.8 mL of 0.15 wt% H2PtCl6 solution under stirring at 450 rpm, stir at room temperature for 1 hour, centrifuge the solution at 12000 rpm for 10 minutes, wash the precipitate obtained by centrifugation twice with ultrapure water to obtain purified Cu 2-x Se@Pt nanomaterials, namely Cu 2-x Se@Pt NPs; purified Cu 2-x Se@Pt NPs were freeze-dried in a vacuum environment and redispersed in ultrapure water to prepare a Cu solution with a concentration of 1 mg / mL. 2-x Se@PtNPs solution for subsequent use.

[0046] Example 3 A Cu 2-x The preparation method of Se@Pt nanomaterials comprises the following steps: S1. Take 5.5 mL of H2O and add it to a round-bottom flask. Then, add 1.6 mL of 10 mg / mL PSS (sodium polystyrene sulfonate), 0.1 mL of 0.2 mol / L SeO2 and 0.3 mL of 0.4 mol / L AA (ascorbic acid) in sequence, and stir at 30°C for 10 minutes. Then, heat the mixture to 45°C and add 0.1 mL of 0.4 mol / L CuSO4•5H2O and 0.4 mL of 0.4 mol / L AA mixed solution under vigorous stirring to obtain a mixture. The obtained mixture is vigorously stirred at 45°C for 8 hours until a green solution is obtained. The obtained green solution is centrifuged at 10,000 rpm for 10 minutes. The precipitate obtained by centrifugation is washed twice with ultrapure water and then purified by 10 kDa dialysis membrane for 24 hours. The purified product Cu 2-x Se was freeze-dried; S2, the Cu obtained in S1 2-x Se was dissolved in water to prepare a concentration of 1 mg / mL Cu 2-x Se solution, dissolve hexahydrate chloroplatinic acid (H2PtCl6·6H2O) in water to prepare a H2PtCl6 solution with a mass percentage of 0.015 wt%; Add 1 mL of 1 mg / mL Cu 2-xSe solution, then 8 mL of ultrapure water was added, and 0.8 mL of 0.015 wt% H2PtCl6 solution was added under stirring at 450 rpm. After stirring at room temperature for 3 hours, the resulting solution was centrifuged at 12000 rpm for 10 minutes. The precipitate obtained by centrifugation was washed twice with ultrapure water to obtain purified Cu 2-x Se@Pt nanomaterials, namely Cu 2-x Se@Pt NPs; purified Cu 2-x Se@PtNPs were freeze-dried in a vacuum environment and redispersed in ultrapure water to prepare a Cu solution with a concentration of 1 mg / mL. 2-x Se@Pt NPs solution for subsequent use.

[0047] Example 4 A method for preparing a microneedle patch comprises the following steps: 1) The photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) was dissolved in PBS solution (0.01 M) to prepare a photoinitiator solution with a mass percentage of 0.25 wt%; then the Cu prepared in Example 1 was added to the solution. 2-x Se@Pt nanomaterial powder was dissolved in a photoinitiator solution with a mass percentage of 0.25 wt% until Cu 2-x The final concentration of Se@Pt nanomaterials was 40 μg / ml, and then methacryloyl hyaluronic acid (HAMA) powder was added to a final concentration of 25 mg / ml and dissolved overnight to obtain Cu 2-x Se@Pt-HAMA mixed solution; 2) Add 400 μl of the Cu synthesized in step 1) to the cleaned PDMS microneedle patch template. 2-x The Se@Pt-HAMA mixed solution was repeatedly defoamed and filled with a vacuum negative pressure of 0.01 Pa (2-3 times), and then dried at 35 °C for 2 h. Subsequently, 200 μl of the Cu synthesized in step 1) was added. 2-x The Se@Pt-HAMA mixed solution was defoamed and dried for 2 h, and the drying and concentration process was repeated 2-3 times; then it was irradiated with a UV lamp at a wavelength of 365 nm for 10 min, and finally demolded to obtain Cu 2-x Se@Pt / MN hydrogel microneedle patch, stored dry.

[0048] Example 5 A method for preparing a microneedle patch comprises the following steps: 1) Dissolve the photoinitiator diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO) in PBS solution (0.01M) to prepare a photoinitiator solution with a mass percentage of 0.25 wt%; then add the Cu prepared in Example 2 2-x Se@Pt nanomaterial powder was dissolved in a photoinitiator solution with a mass percentage of 0.25 wt% until Cu 2-x The final concentration of Se@Pt nanomaterials was 40 μg / ml, and then methacryloyl hyaluronic acid (HAMA) powder was added to a final concentration of 25 mg / ml and dissolved overnight to obtain Cu 2-x Se@Pt-HAMA mixed solution; 2) Add 400 μl of the Cu synthesized in step 1) to the cleaned PDMS template. 2-x The Se@Pt-HAMA mixed solution was repeatedly defoamed, vacuum filled with 0.01 Pa (2-3 times), and then dried at 35 °C for 2 h. Then, 200 μl of Cu synthesized in step 1) was added. 2-x The Se@Pt-HAMA mixed solution was defoamed and dried for 2 h, and the drying and concentration process was repeated 2-3 times; then it was irradiated with a UV lamp with a wavelength of 365 nm for 10 min, and finally demolded to obtain Cu 2-x Se@Pt / MN hydrogel microneedle patch, stored dry.

[0049] Example 6 A method for preparing a microneedle patch comprises the following steps: 1) The photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) was dissolved in PBS solution (0.01 M) to prepare a photoinitiator solution with a mass percentage of 0.25 wt%; then the Cu prepared in Example 3 was added. 2-x Se@Pt nanomaterial powder was dissolved in a photoinitiator solution with a mass percentage of 0.25 wt% until Cu 2-x The final concentration of Se@Pt nanomaterials was 40 μg / ml, and then methacryloyl hyaluronic acid (HAMA) powder was added to a final concentration of 25 mg / ml and dissolved overnight to obtain Cu 2-x Se@Pt-HAMA mixed solution; 2) Add 400 μl of the Cu synthesized in step 1) to the cleaned PDMS template. 2-x The Se@Pt-HAMA mixed solution was repeatedly defoamed, vacuum filled with 0.01 Pa (2-3 times), and then dried at 35 °C for 2 h. Then, 200 μl of Cu synthesized in step 1) was added. 2-xThe Se@Pt-HAMA mixed solution was defoamed and dried for 2 h, and the drying and concentration process was repeated 2-3 times; then it was irradiated with a UV lamp with a wavelength of 365 nm for 10 min, and finally demolded to obtain Cu 2-x Se@Pt / MN hydrogel microneedle patch, stored dry.

[0050] Detection and Analysis 1) Transmission electron microscopy (TEM) analysis The Cu prepared in S1 of Example 1 2-x Cu prepared from Se and S2 2-x Se@Pt nanomaterials were subjected to transmission electron microscopy (TEM) and Cu 2-x Se@Pt nanomaterials were tested by spherical aberration corrected transmission electron microscopy (AC-TEM) and high resolution transmission electron microscopy (HRTEM). Figure 1 shown.

[0051] Figure 1 (a) represents Cu 2-x TEM image of Se, Figure 1 (b) represents Cu 2-x TEM image of Se@Pt nanomaterials, Figure 1 (c) represents Cu 2-x AC-TEM image of Se@Pt nanomaterials, Figure 1 (d) represents Cu 2-x HRTEM image of Se@Pt nanomaterials, Figure 1 (e) indicates Figure 1 (d) The enlarged image of the green frame after Fourier transformation. Figure 1 (f) indicates Figure 1 (d) Enlarged image of the red box after Fourier transformation.

[0052] from Figure 1 As can be seen from (a), Cu 2-x Se is a nanosphere with a diameter of about 40nm. After in-situ reduction and loading of Pt, the microscopic morphology of the nanosphere does not change, but the diameter increases slightly. Figure 1 (b) It can be seen that in Cu 2-x No obvious Pt atoms or clusters were found on the surface of Se nanospheres, indicating that they were single atoms. 2-x The micromorphology of Se@Pt nanomaterials was analyzed. Figure 1 (c) shows Cu 2-x Edge morphology of Se@Pt nanospheres. Figure 1As can be seen in (c), there are some white spots on the edge of the nanosphere (the part circled in red in the figure). These white spots represent the single-atom distribution of Pt elements on the surface of the nanosphere. In addition, the lattice information suggests that the center of the nanosphere (green frame, Figure 1 (e)) and the edge (red frame, Figure 1 (f)) are 0.32nm and 0.200nm, respectively, representing Cu 2-x The (111) and (220) crystal planes of Se nanospheres can also be found to have a certain degree of lattice distortion at the edges, which is caused by the doping of Pt single atoms.

[0053] 2) XRD analysis The Cu prepared in S1 of Example 1 2-x Cu prepared from Se and S2 2-x Se@Pt nanomaterials were tested by XRD respectively. The results are as follows Figure 2 shown.

[0054] from Figure 2 It is known that Cu 2-x The three characteristic peaks of Se correspond to the (111), (220), and (311) crystal planes in PDF#06-0680, proving the successful synthesis of copper selenide. 2-x There is no obvious Pt peak in the XRD spectrum of Se@Pt nanomaterials, indicating that Pt exists in the form of single atoms.

[0055] 3) XPS analysis The Cu prepared in S1 of Example 1 2-x Cu prepared from Se and S2 2-x Se@Pt nanomaterials were tested by XPS. The results are as follows Figures 3 to 5 shown.

[0056] Figure 3 Cu 2-x High-resolution XPS spectrum of Cu 2p orbitals of Se, Figure 4 Cu 2-x High-resolution XPS spectrum of Cu 2p orbitals of Se@Pt nanomaterials. Figure 3 and Figure 4 It can be seen that the Cu element in both materials is in mixed valence state, and the doping of Pt atoms reduces the content of monovalent copper. 2-x SeCu + The content is 75.1%, Cu 2-x The value of Se@Pt nanomaterial (0.015wt%) is 69.4%. After Pt element doping, the valence state of copper element is changed, which affects the catalytic performance and photothermal performance of the material. Figure 5 Cu 2-x The high-resolution XPS spectrum of Pt 4f orbitals of Se@Pt nanomaterials (0.015wt%) Figure 5 It can be seen from the figure that the doping of Pt atoms has no effect on the valence state of Se elements. At the same time, it also confirms the successful loading of Pt atoms.

[0057] 4) Cu 2-x Analysis of catalytic kinetics and catalytic principles of Se@Pt nanomaterials In order to evaluate Cu 2-x Se@Pt nanomaterials are used as nanoenzymes to measure the affinity of the substrate and the catalytic efficiency of the enzyme. In this study, TMB was used as the substrate and the Cu prepared in Example 1 was studied according to the Michaelis equation. 2-x The results show that Se@Pt nanomaterials can be used as nanoenzymes to improve the catalytic efficiency of enzymes. Figure 6 shown.

[0058] Figure 6 (a) is the time-absorbance curve when TMB is 1 mM. Figure 6 (b) is the TMB concentration-rate curve, Figure 6 (c) is the corresponding double reciprocal curve. The Michaelis constant (K m ), maximum reaction rate (V max ) and enzyme conversion number (K cat ) These are the key kinetic parameters for evaluating the affinity of nanozymes to substrates. Among them, K m The value is used as an affinity index, and its value is negatively correlated with the affinity, namely K m The lower the value, the stronger the binding ability of the nanozyme to the substrate. cat It measures the amount of substrate converted by a single enzyme molecule in one second, or the time required for a single enzyme molecule to convert one substrate molecule. Its value is positively correlated with the catalytic efficiency of the enzyme. Figure 6 (c), it can be calculated that when TMB is used as substrate, Cu 2-x K of Se@Pt nanomaterials m 0.132 mM, V max 7.47×10 -8 Ms -1 , K cat 7.33×10 3 S -1 The above data show that when Pt element is distributed in Cu 2-x When the nanozyme binds to the surface of Se nanospheres, the enzyme affinity of the nanozyme is high and the conversion efficiency is high, indicating that the atomic utilization rate of the catalyst is high.

[0059] Density functional theory (DFT) calculations were performed to simulate the Cu 2-xEnergy changes in the catalytic process of Se@Pt nanomaterials as nanozymes. The catalysis of H2O2 is divided into the following steps: (1) H2O2 is adsorbed on the active site to form *H2O2; (2) *H2O2 decomposes into hydroxyl radicals (2*OH); (3) hydroxyl radicals react with H in the environment. + H2O is formed, and then H2O desorbs, leaving the active site empty. Figure 7 shown.

[0060] from Figure 7 It can be seen from the Gibbs free energy diagram in that the key step of the catalytic reaction is the second step, which is the decomposition to generate hydroxyl radicals. Pt element and Cu 2-x Se and Cu 2-x The reaction energy barriers required for the second step of the three materials Se@Pt are 2.037eV, 1.338eV, and 0.396eV, respectively. 2-x Se@Pt nanomaterials as nanoenzymes are more likely to catalyze the decomposition of H2O2. The doping of single atoms can effectively reduce the reaction energy barrier and improve the catalytic efficiency.

[0061] 5) Cu 2-x Peroxidase-like activity test of Se@Pt nanomaterials In order to evaluate Cu 2-x Se@Pt nanomaterials act as nanozymes to catalyze H2O2 to produce hydroxyl radicals (•OH) and singlet oxygen ( 1 O2), this study used DMPO as the scavenger of •OH, and TEMP as 1 O2 capture agent, add H2O2, use the electroparamagnetic resonance (EPR) method to detect the signal of ROS generated, the results are as follows Figures 8 to 10 shown.

[0062] Figure 8 Cu captured by DMPO 2-x Electron paramagnetic resonance (EPR) spectra of •OH (hydroxyl radical) in Se@Pt and H2O2 solutions; Figure 9 Cu captured by TEMP 2-x Electron paramagnetic resonance (EPR) spectra of ¹O2 (singlet oxygen) in Se@Pt and H2O2 solutions; Figure 10 To detect Cu using TMB probe 2-x Catalase-like performance of Se@Pt in the presence of different concentrations of H2O2.

[0063] from Figure 8 and Figure 9 The results show that there are obvious •OH and 1 O2 signal, and the signal intensity increased with time, confirming that Cu2-x Se@Pt nanozymes can catalyze H2O2 to produce ROS. Then, the characteristics of TMB that can be oxidized by ROS to generate oxTMB were used to further evaluate the Cu 2-x The peroxidase-like activity of Se@Pt Figure 10 As can be seen from the figure, with the increase of H2O2 concentration, the absorption peak at 652 nm gradually increases, which once again confirms that Cu 2-x Se@Pt nanozyme exhibits excellent catalase-like activity.

[0064] 6) Cu 2-x Photothermal performance test of Se@Pt nanomaterials According to Cu 2-x Se has unique optical properties. This study explored the optical properties of Cu under 808 nm laser irradiation. 2-x The photothermal properties of Se@Pt were evaluated to evaluate its photothermal therapeutic effect. Figures 11 to 13 shown.

[0065] Figure 11 Cu under 808 nm laser irradiation 2-x Temperature rising curves of Se@Pt (100 μg / ml) at different laser intensities; Figure 12 808 nm laser (1 W / cm 2 ) under different concentrations of Cu 2-x Heating curve of Se@Pt; Figure 13 Under 808 nm laser (1W / cm2), H2O, Cu 2-x Se (100 μg / ml) and Cu 2-x Thermal imaging of Se@Pt (100 μg / ml).

[0066] from Figure 11 As can be seen from the figure, when Cu is irradiated with 808 nm laser 2-x When Se@Pt (100 μg / ml) was used, the 2 , 0.75 W / cm 2 , 1 W / cm 2 and 1.25 W / cm 2 At an optical density of , the solution temperature rose to 48.42 ° C, 57.26 ° C, 66.69 ° C and 71.94 ° C after ten minutes, indicating that Cu 2-x The photothermal performance of Se@Pt is positively correlated with its optical density. Figure 12 The results shown are at 1 W / cm 2 At an optical density of 2-x The heating curve of Se@Pt Figure 12It can also be seen that the photothermal performance is positively correlated with the material concentration. Figure 13 Compared with 808 nm laser (1 W / cm 2 ) irradiation, H2O, Cu 2-x Se (100 μg / ml) and Cu 2-x Photothermal performance of Se@Pt (100 μg / ml), from thermal imaging Figure 13 It can be clearly seen that after 10 min of irradiation, H2O hardly heats up, while Cu 2-x Se and Cu 2-x Se@Pt can be heated to about 55℃, and Cu 2-x The temperature of Se@Pt is slightly higher than that of Cu 2-x Se.

[0067] 7) Cu 2-x Characterization of Se@Pt hydrogel microneedle patches The Cu prepared in Example 4 was observed using an optical microscope. 2-x Se@Pt / MN hydrogel microneedle patch was tested and the Cu 2-x Optical images of Se@Pt / MN hydrogel microneedle patch Figure 14 (a) The Cu prepared in Example 4 was observed by scanning electron microscopy. 2-x Se@Pt / MN hydrogel microneedle patch was tested and the Cu 2-x SEM images of Se@Pt / MN hydrogel microneedle patch Figure 14 (b) and Figure 14 (c) Figure 14 (c) Figure 14 A local enlarged view of the blue rectangular box in (b).

[0068] from Figure 14 As can be seen from (a), the microneedle part is in the shape of a quadrangular pyramid. Figure 14 From the SEM results in (c), it can be seen that the microscopic morphology of the microneedle patch is relatively rough. Such a rough quadrangular pyramidal microneedle structure is more conducive to deep contact with the wound skin and can effectively deliver nanozymes.

[0069] The Cu prepared in Example 4 was irradiated with 808 nm laser. 2-x Se@Pt / MN, at 1 W / cm 2 The photothermal performance under optical density was used to evaluate its photothermal therapeutic effect. Figure 15 and Figure 16 shown.

[0070] from Figure 15 It can be seen that Cu 2-xAfter Se@Pt nanozyme was encapsulated in the microneedle patch, it still maintained excellent photothermal performance, which was different from the microneedle patch without nanozyme (i.e. Figure 15 Compared with the control in 2-x The temperature of Se@Pt / MN rose to about 56°C within 10 minutes and to 40°C within 2 minutes. The microneedle patch in the control group (microneedle patch without nanozymes) heated up slowly, and the temperature change was not obvious after 10 minutes.

[0071] Figure 16 The heating curve in FIG. 4 illustrates this phenomenon more intuitively, which proves that the Cu 2- x Se@Pt / MN has excellent photothermal properties and has an enhanced effect on wound treatment. This study used a texture analyzer to characterize the blank microneedle patch and Cu 2-x Hardness of Se@Pt / MN.

[0072] Figure 17 The figure shows the force that the microneedle can withstand when the displacement of the microneedle tip changes from 0 to 0.5 mm. Figure 17 It can be seen that the Cu prepared in Example 1 2-x After Se@Pt was added to the microneedle, the hardness of the microneedle tip decreased, but the degree of decrease was not high, indicating that the Cu prepared in Example 4 2-x Se@Pt / MN has sufficient hardness to penetrate deep into the wound.

[0073] In order to study Cu 2-x The drug release of Se@Pt / MN was studied. In this study, the Cu prepared in Example 4 was used to 2-x Se@Pt / MN was placed in PBS solution, and the content of Pt element in PBS at different times was measured by ICP-MS to evaluate the Cu 2-x The drug release ability of Se@Pt / MN is shown in the following table. Figure 18 shown.

[0074] from Figure 18 It can be seen that after 12 min, Cu 2-x The release efficiency of Se@Pt / MN reached more than 60%, indicating that Cu 2-x Se@Pt / MN has good drug release efficiency, which is beneficial to increasing the wound treatment effect.

[0075] 8) Cu 2-x In vitro antibacterial experiments of Se@Pt nanomaterials Drug-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E. coli) were selected as models of Gram-positive and Gram-negative bacteria, respectively, to determine the Cu prepared in Example 1. 2-x Se and Cu 2-x In vitro antibacterial properties of Se@Pt NPs.

[0076] The specific operation is as follows: after turbidimetric dilution, take 160 μL of bacterial suspension into a test tube, add 20 μL of H2O2 (1 mM), 20 μL of Cu 2-x Se / Cu 2-x Se@Pt (1 mg / mL) solution was added to make the final concentration of bacterial solution 1×106 CFU / mL, the final concentration of H2O2 was 100 μM, and the final concentration of Cu 2-x Se / Cu 2-x The final concentrations of Se@Pt nanomaterials were 0, 10, 20, 40, 80, and 100 μg / mL, respectively, with a total of 12 groups. The preparations of 13) to 24) were the same as those of 1) to 12), and 0.75 W of 808 nm near-infrared light was added for 10 min. After the preparation of 1) to 12), they were directly incubated for 1 hour. After the preparation of 13) to 24), they were illuminated for 10 minutes and then incubated for 50 minutes. There were 3 parallels in each group. After the incubation of the above groups, 100 μL of the above suspension was taken from each group to the LB plate, and the suspension was shaken up and down with sterile glass beads. It was then moved into the incubator and cultured for 24 hours. The number of colonies was recorded and photographed. After the same treatment as above, SEM photography and bacterial live and dead staining were performed to detect the multifunctional Cu 2-x Se@Pt nanozymes inhibited the growth of drug-resistant Staphylococcus aureus and Escherichia coli (E. coli). Figure 19 shown.

[0077] Figure 19 (a) Cu 2-x Se / Cu 2-x Killing effect of Se@Pt NPs on bacteria (MRSA / E. coli); Figure 19 (b) The killing effect of bacteria by combining photothermal effect and catalysis. Figure 19 (a) and Figure 19 As can be seen from (b), Cu 2-x Se / Cu 2-x Se@PtNPs have a certain degree of killing effect on both bacteria (MRSA / E. coli), and the inhibition ability depends on the Cu 2-x Se / Cu 2-x The concentration of Se@Pt NPs, 80 μg / mL Cu 2-x Se / Cu 2-x Se@Pt NPs can inhibit the growth of most bacteria.2-x Se / Cu 2-x The antibacterial effect of Se@Pt NPs may be caused by catalyzing the Fenton reaction of H2O2 highly expressed in bacteria.

[0078] To further investigate Cu 2-x Se / Cu 2-x The antibacterial properties of Se@Pt NPs were analyzed. The bacteria were grouped as follows: (1) blank, (2) NIR (near infrared laser), (3) H2O2, (4) H2O2 + NIR, (5) Cu 2-x Se NPs, (6)Cu 2-x Se NPs + NIR, (7)Cu 2-x Se@Pt NPs, (8)Cu 2-x Se@Pt NPs + NIR, (9)Cu 2-x Se NPs + H2O2, (10)Cu 2-x Se NPs +H2O2 + NIR, (11)Cu 2-x Se@Pt NPs + H2O2, (12)Cu 2-x Se@Pt NPs + H2O2+ NIR. The results are as follows Figure 20 shown.

[0079] from Figure 20 It can be seen that the colony counts in the H2O2 group and the 808 nm near-infrared laser (NIR) group were similar, both close to the blank group, indicating that the antibacterial effect of H2O2 (100 μM) alone was weak. 2-x Se / Cu 2-x The antibacterial effect of Se@Pt NPs was significantly enhanced after adding H2O2 and irradiating with light (808 nm, 0.75 W, 10 min), especially the antibacterial effect of Cu 2-x The killing effect of Se NPs groups (5, 6, 9, 10) on bacteria was better than that of Cu 2-x The Se@Pt NPs group (7, 8, 11, 12) is stronger because its own toxicity is very strong, and we modified its surface with Pt NPs to change its configuration and reduce its own physiological toxicity. The bactericidal effect directly observed by live / dead staining of bacteria after the same treatment is consistent with this ( Figure 20 ). These results indicate that Cu 2-x Se / Cu 2-x Se@PtNPs can combine with Cu 2-x The physiological toxicity of Se NPs, catalysis of H2O2 to produce •OH, and the antibacterial effect achieved by combining with the photothermal effect. Overall, the bacterial morphological damage caused by the combined treatment group (Cu 2-xSe@Pt NPs + H2O2 + NIR) was the most serious and had the best antibacterial effect.

[0080] 9) Cu 2-x Se@Pt / MN animal wound treatment To further evaluate Cu 2-x Se@Pt NPs have a wound healing effect on chronic wounds. We established MRSA-infected wounds for in vivo experiments.

[0081] Specifically, 6-8 week old BALB / C mice (male, 20±2 g) were purchased and acclimated for one week in a constant temperature and humidity environment (25±1°C, 50±5% humidity), with adequate food and water, and a 12-12 h light-dark cycle. In subsequent experiments, the mice were randomly divided into 7 groups (n=6): ① blank control group (Con), ② laser irradiation group (NIR), ③ H2O2 group (H2O2), ④ Cu 2-x Se@Pt hydrogel microneedle group (Cu 2-x Se@Pt MN), ⑤Cu 2-x Se@Pt hydrogel microneedle + H2O2 group (Cu 2-x Se@Pt MN + H2O2), ⑥Cu 2-x Se@Pt hydrogel microneedle + laser irradiation group (Cu 2-x Se@Pt MN + NIR), ⑦Cu 2-x Se@Pt hydrogel microneedle + H2O2 + laser irradiation group (Cu 2-x Se@Pt MN + H2O2 + NIR). After anesthesia, a full-thickness wound model with a diameter of 8 mm was established on the back of the animal, and drug-resistant Staphylococcus aureus solution (1×10 9 CFU / mL, 100μL) to create infected wounds. Figure 21 On the first 2 days of treatment, a full-thickness wound model with a diameter of 8 mm was established on the back of Balb / c mice after anesthesia, and drug-resistant Staphylococcus aureus solution (1×10 9 CFU / mL, 50μL) to create infected wounds. The mice were divided into groups for treatment on day 0, and the wound healing status (whether scabs formed, wound size, etc.) and weight changes of the mice were recorded on days 0, 2, 4, 6, and 8 of treatment. Figure 22 shown.

[0082] Figure 22 (a) Representative photos of wounds at different time points. Figure 22 (b) is a simulated image of the wound during treatment. Figure 22 (c) is the statistical analysis of wound area, Figure 22 (d) Cu during treatment 2-x Infrared thermal imaging of Se@Pt MN after laser irradiation.

[0083] from Figure 22 (ac) shows that Cu 2-x Se@Pt MN combined with H2O2 catalysis and laser irradiation photothermal group (Cu 2-x The recovery rate of mice with Se@PtMN + H2O2 + NIR was the fastest. On the 8th day, the wounds of mice in this group had healed, with a wound healing rate of 93.9% and no obvious trauma was visible. 2-x Se@Pt MN can combine with Cu 2-x The photothermal properties of Se NPs themselves ( Figure 22 (d)), Cu after laser irradiation 2-x Se@Pt MN can reach 46.1℃, and after loading Pt NPs, it catalyzes ROS at the wound site to kill bacteria and promote wound healing.

[0084] In summary, the present invention Cu 2-x Se@Pt nanomaterials were synthesized by stirring in a water bath. 2-x Se nanoparticles, and then H2PtCl6 (0.015wt%, 0.15wt%) was used as the Pt source in the Cu 2-x Se surface was modified by in situ reduction to obtain Cu 2-x Se@Pt nanoparticles. The experimental results show that the Pt atoms with single atomic distribution have excellent catalytic performance, and the introduction of Pt atoms reduces the energy barrier of the catalytic reaction and improves the catalytic performance. At the same time, the introduction of Pt changes the Cu 2-x The valence state of Cu in Se makes Cu 2-x The photothermal performance of Se has been improved. In addition, in terms of biosafety, the loading of Pt atoms has greatly reduced the biotoxicity of the material. 2-x Se@Pt nanoparticles combined with photothermal therapy (PTT) and chemodynamic therapy (CDT) can induce the rapid death of multidrug-resistant bacteria. In vitro cell experiments and sterilization experiments have demonstrated that Cu 2-x Biosafety and efficient ROS generation ability of Se@Pt nanomaterials.

[0085] Cu 2-x Se@Pt hydrogel microneedle patch, by using PDMS (polydimethylsiloxane) as the microneedle patch template and HAMA (methacryloylated hyaluronic acid gelatin) as the hydrogel carrier, first prepare HAMA-Cu 2-xThe Se@Pt mixed solution was then poured into the template and the Cu@Pt was prepared through vacuum negative pressure filling, drying and concentration, photocuring and demoulding. 2-x Se@Pt hydrogel microneedle patch (Cu 2-x Se@Pt / MN). According to the test, Cu 2-x Se@Pt hydrogel microneedle patch as a carrier of nano-drugs can penetrate biological membranes and achieve deep drug delivery, ensuring efficient local drug release and avoiding systemic toxicity. 2-x Se@Pt / MN acted on the wounds of mice and accelerated the healing of the wounds under 808 nm laser irradiation. Therefore, it has the value of promotion and application in the field of biomedical materials technology.

[0086] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or modification made by those skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A Cu 2-x Se@Pt nanomaterials are characterized by: By Cu 2-x Se nanospheres and in situ modification of the Cu 2-x Pt composition on the surface of Se nanospheres; Among them, the value of x is: 0 <x<2。 2. Cu according to claim 1 2-x Se@Pt nanomaterials are characterized by: The Pt is supported in the Cu 2-x Surface of Se nanospheres.

3. Cu according to claim 1 or claim 2 2-x The preparation method of Se@Pt nanomaterial is characterized in that: The following steps are involved: S1. Add sodium polystyrene sulfonate (PSS), selenium dioxide (SeO2) and ascorbic acid (AA) to water, then stir under the first temperature, raise the temperature to the second temperature, add a mixed solution of copper salt and ascorbic acid under stirring, vigorously stir the reaction to obtain a green solution, centrifuge, wash, purify, and obtain Cu 2-x Se; S2, to Cu 2-x Se was added with water and hexachloroplatinic acid (H2PtCl6) solution, stirred for reaction, centrifuged, washed, and purified to obtain Cu 2-x Se@Pt nanomaterials.

4. Cu according to claim 3 2-x The preparation method of Se@Pt nanomaterial is characterized in that: The first temperature is 25-35° C., and the stirring time under the first temperature condition is 8-12 minutes; And / or, the second temperature is 40-50°C; And / or, in said S1, the temperature of the vigorous stirring reaction is 40-50°C and the time is 7-9h; And / or, in S2, the stirring reaction temperature is room temperature and the time is 0.8 to 1.2 hours; and / or, the copper salt is selected from copper sulfate and / or copper sulfate pentahydrate (CuSO4•5H2O); And / or, the molar ratio of copper salt to ascorbic acid in the mixed solution of copper salt and ascorbic acid is 1:

4.

5. Cu obtained by the preparation method according to claim 3 or claim 4 2-x The application of Se@Pt nanomaterials is characterized by: The Cu 2-x Se@Pt nanomaterials are used to prepare drugs against drug-resistant bacteria; and / or, the Cu 2-x Se@Pt nanomaterials as photothermal conversion materials; and / or, the Cu 2-x Se@Pt nanomaterials are used as p-type semiconductor nanocrystal materials; and / or, the Cu 2-x Se@Pt nanomaterials as Fenton-like reagents; and / or, the Cu 2-x Se@Pt nanomaterials as nanozymes.

6. The use according to claim 5, characterized in that The drug-resistant bacteria include carbapenem-resistant bacteria and methicillin-resistant bacteria.

7. A microneedle patch, characterized in that: Comprising hyaluronic acid and Cu prepared by the preparation method according to any one of claim 3 or claim 4 2-x Se@Pt nanomaterials.

8. The method for preparing the microneedle patch according to claim 7, wherein: The following steps are involved: 1) Cu 2-x Se@Pt nanomaterials were dissolved in a photoinitiator, and hyaluronic acid was added to obtain a mixed solution; 2) The mixed solution is loaded into a mold, defoamed, vacuum-filled, dried, irradiated with ultraviolet light, and demolded to obtain a hydrogel microneedle patch.

9. The method for preparing the microneedle patch according to claim 8, wherein: The photoinitiator is selected from lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) and / or diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO); and / or, the hyaluronic acid is selected from methacryloyl hyaluronic acid (HAMA); And / or, the drying temperature is 30-40° C. and the drying time is 1.5-4.5 h; And / or, the wavelength of the ultraviolet lamp is 365 nm, and the irradiation time is 8 to 12 minutes.

10. Use of the microneedle patch prepared by the preparation method according to claim 8 or claim 9 in the preparation of drugs against drug-resistant bacteria.

Citation Information

Cited By

  • Multi-stage microporous titanium alloy loaded with nano copper selenide antibacterial peptide and preparation method of multi-stage microporous titanium alloy

    CN121265852A

  • Photothermal-thermoelectric synergistic catalysts and their preparation methods and alcoholysis methods for polyester plastics

    CN122399848A